Decline and preservation of reversal learning abilities and acquisition in the course of senescence - Rahner-Welsch, Sylvia; Frölich, Lutz; Stoll, Siegfried; Hoyer, Siegfried (Neuroscience letters, 1995)
Different types of learning and memory functions decrease at different rates in senescence. The present study examines which types of mental functions show a relatively early decline and which learning abilities are relatively preserved in late senescence by investigating different types of learning abilities in water maze tests. Two groups of senescent male Wistar rats aged 24 months (group W24) and 30 months (group W30), respectively, were compared to adult rats (12 months, group W12). Group W24 represents ‘senescent’ and group W30 ‘late-senescent’ rats. Whereas acquisition showed a relatively late decline (in group W30), reversal learning was impaired relatively early (group W24).